Novel Algorithm for Surgical Management of Cervical Ossification of Posterior Longitudinal Ligament: A Retrospective Cohort Study With 2‐Year Follow‐Up - Zhuyun Cai; Hui Kang; Lei Quan; Yilong Ren; Meng Fang; Yixuan Tan; Haochen Zhang; Xuhui Zhou; Jun Ma (Orthopaedic Surgery)
ABSTRACT Object With the development of new technologies, the surgical algorithm for ossification of posterior longitudinal ligament (OPLL) in the cervical spine also needs to be updated. The aim of this study is to elucidate a new surgical classification algorithm to guide the choice of surgical approaches for cervical OPLL based on its location and extent. In this algorithm, anterior controllable antedisplacement and fusion (ACAF) will be used as a new surgical option. Methods This is a single‐centered, retrospective, cohort study utilizing a novel algorithm based on the following three criteria: (1) the positional relationship between ossification and uncinate process (UP), (2) the K‐line, and (3) the ossification segment for surgical decision‐making. Patients diagnosed with cervical OPLL who received surgical intervention guided by the algorithm were included. Patient demographics, Japanese Orthopedic Association (JOA) scores, surgical time, imaging data before and 2 years after surgery, and the occurrence of complications were extracted from the database. Paired t‐test was used for intragroup comparison, and one‐way ANOVA test was used for the intergroup analyses. Results Based on this novel algorithm, 15 patients with Type I, 8 patients with Type II a, 2 patients with Type II b1, 5 patients with Type II b2 were included. The decision‐making for the surgical techniques used in each patient followed the recommendation of the novel algorithm. The postoperative JOA scores of all types of patients improved significantly (p < 0.05), and the invasion rates of vertebral canal had also been significantly reduced (p < 0.05). In terms of restoring cervical curvature, patients with Type I (receiving ACAF) and Type II b2 (receiving laminectomy with instrumented fusion) benefited more from surgery (p < 0.05). Conclusion A new algorithm guiding the choice of surgical approach for cervical OPLL was validated in a series of 30 patients. Through this analysis, we obtained on their clinical outcomes and complications. ACAF surgery is an ideal choice for Type I patients, with ossification located between UPs, while for patients with ossification exceeding UPs, it is better to perform anterior cervical corpectomy and fusion or posterior surgery.